2017
DOI: 10.3389/fpls.2017.01890
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Cytological Analyses of the Natural Variation of Seed Number per Pod in Rapeseed (Brassica napus L.)

Abstract: Seed number is one of the key traits related to plant evolution/domestication and crop improvement/breeding. In rapeseed germplasm, the seed number per pod (SNPP) shows a very wide variation from several to nearly 30; however, the underlying causations/mechanisms for this variation are poorly known. In the current study, the genetic and cytological bases for the natural variation of SNPP in rapeseed was firstly and systematically investigated using the representative four high-SNPP and five low-SNPP lines. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Previous studies have shown that the number of ovules per ovary, the proportion of fertile ovules, the proportion of fertile ovules to be fertilized, the proportion of fertilized ovules all determined the seed number per silique (Li et al, 2014;Li S. et al, 2015;Yang et al, 2017). The above experimental results showed that the number of ovules per ovary and the proportion of fertile ovules had no difference between NIL-Zhongshang11 and NIL-No.…”
Section: Cytological Analysis Of Qsna7mentioning
confidence: 54%
See 4 more Smart Citations
“…Previous studies have shown that the number of ovules per ovary, the proportion of fertile ovules, the proportion of fertile ovules to be fertilized, the proportion of fertilized ovules all determined the seed number per silique (Li et al, 2014;Li S. et al, 2015;Yang et al, 2017). The above experimental results showed that the number of ovules per ovary and the proportion of fertile ovules had no difference between NIL-Zhongshang11 and NIL-No.…”
Section: Cytological Analysis Of Qsna7mentioning
confidence: 54%
“…The previous studies have investigated the regulatory mechanisms of seed number per silique difference between the different cultivars, through cytological observation using several techniques. The results showed that ovule number and fertility, double fertilization and seed development all affect the final seed number per silique, although their relative contributions might differ in different cultivars (Li et al, 2014;Li S. et al, 2015;Yang et al, 2017).…”
Section: The Regulatory Mechanism Of the Seed Number Per Silique In Rmentioning
confidence: 94%
See 3 more Smart Citations